DEVELOPMENT OF PACK-TO-CELL BATTERY BALANCING SYSTEM USING COMPLEMENTARY ACTIVE TRANSFER METHOD - Anandika, Mugi
Due to the regulation of renewable energy, the need for Battery Energy Storage Systems for both mobile and stationary applications is increasing. To meet the demand for power consumption, several of individual battery cells must be arranged in a series-parallel configuration on a system called a battery pack. However, the series configuration in a battery pack causes a new problem. It will causes the imbalance of charge on each individual battery cell. Therefore the need of an adequate and efficient battery charge balancing system is a must to extend the life of each battery cell. A good battery balancing system is required to be able to keep the state of charge level of each individual battery cell at the same level. In this final project, a balancing system will be designed using a pack to cell topology with a complementary active transfer method of two capacitors. To build the system, an arduino microcontroller will be used. This microcontroller have responsibility to control all the switch in this system. Switching decision will be processed based on the voltage and current sensor information contained in each cell and battery pack. The charge will flow from the high voltage battery pack to the DC-DC converter and decreasing the charge voltage to its operational range. Then this charge will be temporarily stored in the capacitor to isolate the source and target, so that the charge will safely forwarded to the targeted battery cell. The designed pack to cell battery balancing system works using 2 capacitors that work alternately in charging and discharging energy. This working mechanism can effectively transfer energy so that this system will have a relatively higher efficiency and load transfer performance. In addition, due to the use of a pack-to-cell topology, this balancing system also has a fairly simple complexity, so that the switch workload and component costs can be minimized. With these advantages, the rate of degradation on battery cells will be reduced so that the life of the battery pack will be longer. From the proposed battery balancing design and the tests that have been done, the pack to cell topology with complementary active transfer methods and zero current switching (a combination of inductor and capacitor) at no-load conditions is able to balance the battery with an efficiency of 93.31% and a balancing speed that is faster than the use of 1 capacitor or 2 capacitors alone with a time of 1230 seconds. In addition, the output current produced is also more stable than the use of capacitors alone with a standard deviation of 17.3.